Pengaruh Keragaman Produk, Kewajaran Harga, dan Servicescape terhadap Kepuasan Konsumen di Warmindo Triasta Kecamatan Bojong Kabupaten Pekalongan - Aprilia, Nur Aisyah; Nugraha, Aditya Agung (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The culinary business is one of the business fields that is experiencing very tight competition. This is because many human ideas are increasingly innovative and creative, but the presence of rivalry in the business world is something that cannot be eliminated. One type of business that faces very tight competition is Warmindo. The aim of this research is to determine the influence of product diversity, price fairness and servicescape on consumer satisfaction in Warmindo Triasta, Bojong District, Pekalongan Regency. This research is a type of quantitative research. The data collection method in this research is a questionnaire method using a sample of 100 respondents. The sampling technique uses the accidental sampling method. This research uses a multiple linear regression test data analysis method with the help of SPSS 26. The research results show that partially product diversity, price fairness and servicescape have a positive and significant effect on consumer satisfaction in Warmindo Triasta, Bojong District, Pekalongan Regency. Then simultaneously, product diversity, price fairness and servicescape also influence consumer satisfaction at Warmindo Triasta, Bojong District, Pekalongan Regency.